The prognostic and clinicopathological value of HALP score in non-small cell lung cancer - Li, Qin; Chen, Mengqi; Zhao, Huaqin; Zeng, Jiawei (Frontiers in Immunology, 2025)
ObjectiveThe prognostic role of the hemoglobin, albumin, lymphocyte, and platelet (HALP) score in non-small cell lung cancer (NSCLC) has been widely reported, but the results remain controversial. Therefore, we aim to evaluate the prognostic and clinicopathological value of the HALP score in NSCLC through a pooled analysis.MethodsWe conducted a comprehensive literature search of PubMed, Embase, Web of Science, Cochrane Library, and the ClinicalTrials.gov databases in December 2024 to identify studies evaluating the relationship between the pretreatment HALP score and outcomes in NSCLC patients. Eligible studies included patients treated with surgical resection, chemotherapy, or immunotherapy. The HALP score was calculated using peripheral blood levels of hemoglobin, albumin, lymphocytes, and platelets measured before treatment. Data were extracted and analyzed to determine the association of the HALP score with overall survival (OS), disease/progression/recurrence-free survival (DFS/PFS/RFS), and clinicopathological characteristics. Subgroup and sensitivity analyses were performed to ensure the robustness and reliability of the results.ResultsA total of 10 studies involving 7024 patients were included. The results demonstrated that patients with lower pretreatment HALP score had worse OS (hazard ratio [HR] = 1.73, 95% confidence interval [95% CI]: 1.27-2.34, p < 0.001) and DFS/PFS/RFS (HR = 1.86, 95% CI: 1.30-2.64, p < 0.001). The results remained consistent across subgroup analyses based on study characteristics and sensitivity analyses. Additionally, a lower HALP score was significantly associated with age (odds ratio [OR] = 1.43, 95% CI: 1.15-1.78, p = 0.001) and tumor size (OR = 0.54, 95% CI: 0.38-0.76, p < 0.001).ConclusionsThe HALP score is a valuable prognostic biomarker for predicting survival outcomes in NSCLC patients. Its ability to integrate multiple aspects of systemic inflammation and nutritional status makes it a promising tool for improving risk stratification and guiding treatment decisions. Future studies should continue to validate this finding in prospective, multicentre trials.